Māori in the trading world: Conventional & emerging opportunities - Chris Nixon; Rebecca Schrage (New Zealand Institute of Economic Research (NZIER), 2005)
[1. Introduction] This chapter examines New Zealand's participation in export trade: [2] section 2 explores why international trade is important and sets out some key concepts and issues [3] section 3 examines trends in world trade, to help understand the context in which New Zealand trade is occurring [4] section 4 examines New Zealand's recent export performance [5] section 5 examines the prospects for key industries and sectors and the links with Māori business activities.
Keywords: 330; Maori; Außenhandelsliberalisierung; Außenhandelswirtschaft; Neuseeland